Pembagian Harta Warisan Masyarakat Bugis wajo di Desa Tangkit Baru Kecamatan Sungai Gelam - ERMA NOVITA VERANITA; Indriya Fathni (Universitas Jambi, Fakultas Hukum, 2022)
The purpose of this study was to identify and analyze the implementation of inheritance distribution in the Bugis Wajo community in Tangkit Baru Village and to find out what factors influence the non-implementation of Islamic inheritance law in full in Tangkit Baru Village. The methodology used in this research is the Juridical Empirical research method, namely legal research that analyzes and examines the workings of law in society. Based on the research, that in the Wajo Bugis community in Tangkit Baru Village there was a transition (change) in the distribution of inheritance contained in the Bugis traditional seloko